(untitled) (Equilibrium: Jurnal Pendidikan, 2023)
Abstract. The purpose of this study is to find out more about how village government policies support rural community empowerment programs through the utilization of the Village Fund Budget in Tanggilingo Village. This researcher uses a descriptive type of qualitative approach. This data collection was carried out through observation and interviews using interview guidelines submitted to a number of informants. The results of the study show that the village government does not involve the community in MSME activity programs. In the stages of the empowerment program that utilize village budget funds that are not as planned. Unclear information about the village budget. What the village government is doing is still lacking because the government only steps down once a year. It is suggested that the village government should involve the community in planning the empowerment program. The village government provides assistance in every community empowerment program. The village government is more open and delivers the budget used in the empowerment program that utilizes the Village Fund. The village government evaluates on a scale so that the empowerment program runs well. Keywords: Utilization of village funds, community empowerment Abstrak. Tujuan penelitian ini adalah untuk mengetahui lebih dalam mengenai bagaimana kebijakan pemerintah desa dalam menunjang program pemberdayaan masyarakat pedesaan melalui pemanfaatan Anggaran Dana Desa di Desa Tanggilingo. Peneliti ini menggunakan jenis deskriptif pendekatan Kualitatif. Pengumpulan data ini dilakukan melalui observasi dan wawancara menggunakan pedoman wawancara yang diajukan kepada sejumlah informan. Hasil penelitian menunjukan bahwa Pemerintah desa kurang melibatkan masyarakat di dalam program kegiatan UMKM. Di dalam tahapan program pemberdayaan yang memanfaatkan dana desa anggaran yang tidak sesuai yang direncanakan. Informasi yang kurang jelas tentang anggaran dana desa. Yang dilakukan pemerintah desa masih kurang karena pemerintah hanya turun satu tahun satu kali saja. Disarankan pemerintah Desa harus melibatkan masyarakat di dalam perencanaan program pemberdayaan. Pemerintah desa melakukan pendampingan di dalam setiap program pemberdayaan masyarakat. Pemerintah desa lebih terbuka dan melakukan penyampaian terhadap anggaran yang digunakan dalam program pemberdayaan yang memanfaatkan Dana Desa. Pemerintah desa melakukan evaluasi secara berskala agar program pemberdayaan berjalan dengan baik. Kata Kunci : Pemanfaatan dana desa,pemberdayaan masyarakat